The anatomic feasibility of thoracic branched endoprosthesis in the treatment of blunt thoracic aortic injury - Rogalska, Anna; Flinn-Patterson, Ashley; Navarro, Maria; Combs, Stephanie; Hart, Theodore; Causey, Marlin (Frontiers in Surgery, 2026)
IntroductionBlunt thoracic aortic injury (BTAI) is one of the leading causes of death among trauma patients who sustain high impact thoracic trauma with rapid deceleration. Thoracic endovascular aortic repair (TEVAR) is indicated in high grade injuries and requires a management strategy for the left subclavian artery (LSA). Gore TAG thoracic branch endoprosthesis (TBE) is a newly approved TEVAR device for to maintain LSA patency utilizing a side branch with reported use in acute indications. The anatomic suitability of this device for a population of BTAI patients and optimal inventory for off-the-shelf emergent repairs has not been reported.MethodsA retrospective analysis of 66 patients admitted to a Level 1 Trauma Center who sustained BTAI between January 2011 and December 2023 and underwent TEVAR was performed. Computed tomography imaging was analyzed on all patients to determine the suitability for repair according to instructions for use (IFU) criteria of the manufacturer.ResultsThe distance between the LSA and the injury was less than 2 cm in 59% of patients, representing a possible indication for TBE. The average injury distance in this cohort was 9 mm from the LSA, with 82% of these patients meeting IFU requirements for TBE and 18% requiring standard TEVAR. For patients who met TBE graft requirements, 28 mm, 31 mm, and 34 mm aortic components fit 76% of patients and 10 mm and 12 mm subclavian branches fit 87% of patients. Patients who did not meet IFU requirements for TBE were sized for standard TEVAR with 26 mm, 31 mm, and 34 mm grafts treating 66% of patients.ConclusionsThis study demonstrates key anatomic considerations and models the suitability and optimal TBE inventory drawn from a real-world population of BTAI patients. Despite a vast device catalog for TEVAR, this study demonstrates that carrying three TBE aortic components, two TBE subclavian components, and three standard TEVAR sizes would treat 71% of BTAI patients.